Skeletal Muscle - Ruegg, Markus; Rossi, Fabio; Campbell, Kevin P.; Glass, David; Rudnicki, Michael A.; Birchmeier, Carmen; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
The only open access journal in its field, Skeletal Muscle publishes novel, cutting-edge research and technological advancements that investigate the molecular mechanisms underlying the biology of skeletal muscle. Reflecting the breadth of research in this area, the journal welcomes manuscripts about the development, metabolism, the regulation of mass and function, aging, degeneration, dystrophy and regeneration of skeletal muscle, with an emphasis on understanding skeletal muscle, its maintenance, and its interactions with non-muscle cell types and regulatory modulators. We are particularly interested in mechanistic work on skeletal muscle using animal or iPSC-derived models. We also welcome Methods and Resource papers, within the research article category, to the journal. Main areas of interest include: differentiation of skeletal muscle atrophy and hypertrophy of skeletal muscle aging of skeletal muscle regeneration and degeneration of skeletal muscle biology of muscle stem cells and other muscle resident cell types dystrophic degeneration of skeletal muscle energy and glucose homeostasis in skeletal muscle neuromuscular diseases, ranging from congenital diseases such as Spinal Muscular Atrophy to acquired diseases such as inflammatory myopathies. maintenance of neuromuscular junctions other relevant aspects of skeletal muscle biology In addition, articles on translational work or clinical studies that address molecular and cellular mechanisms of skeletal muscle will be published. Work that describes new methods to assess skeletal muscle function and pathology is welcome. Skeletal Muscle reflects the breadth of research on skeletal muscle and bridges gaps between diverse areas of science for example cardiac cell biology and neurobiology, which share common features with respect to cell differentiation, excitatory membranes, cell-cell communication, and maintenance. Suitable articles are model and mechanism-driven, and apply statistical principles where appropriate; purely descriptive and studies that rely only on C2C12 or similar myogenic cell lines are of lesser interest. .
Keywords: Cytology; Developmental biology; Biochemistry; Bioinformatics; Biotechnology; Cell Biology; Developmental Biology and Stem Cells; Chemical Biology; Computational and Systems Biology; Biotechnology